Numerical calculation of coupled damage effects on ship subjected to internal blast loading of warhead - Hu ZHOU; Xuesen YUE; Xiangshao KONG; Cheng ZHENG; Weiguo WU (Zhongguo Jianchuan Yanjiu, 2022)
ObjectiveThis paper studies the coupled damage effects of a ship's structure due to the internal blast loading of a warhead. MethodsBlast tests with cased charge data are conducted to verify the effectiveness of the coupled SPH-FEM approach, and numerical calculations are then performed on real ship compartment scale model tests to analyze the coupled fragmentation and shockwave damage effects of an explosion in a confined cabin.ResultsThe results show that the fragments caused by the detonation of the warhead will first cause local damage to the cabin structure. The shockwave will exacerbate the local damage, and blasted openings will further increase the space for the propagation and diffusion of the shockwave inside the chamber, which will in turn cause damage to the adjacent structures. The simple equivalence of the warhead to a bare charge does not give a true picture of the effect of the warhead on the ship's structure, and fragmentation plays a significant role in the detonation of the warhead.ConclusionsThe results of this study show that employing the coupled SPH-FEM numerical method to calculate the coupling damage effects on a ship's structure can accurately reproduce the warhead damage pattern in tests, thereby providing support for the improved assessment of the damage of naval structures under warhead detonation.